Consumption-oriented policy instruments for fostering greenhouse gas mitigation. (22nd April 2020) - Grubb, Michael; Crawford-Brown, Doug; Neuhoff, Karsten; Schanes, Karin; Hawkins, Sonja; Poncia, Alexandra
ABSTRACT: Most policy instruments to reduce greenhouse gas (GHG) emissions have focused on producers, and on the energy efficiency of buildings, vehicles and other products. Behavioural changes related to climate change also impact 'in-use' emissions, and potentially, emissions both 'upstream' (including from imported goods) and 'downstream' (eg disposal). Consumption-oriented policies may provide avenues to additional and cost-effective emission reductions, but are less prevalent, in part because of political sensitivities around government efforts to shape individual-level mitigation behaviour. In this paper, we explore policy instruments for encouraging low carbon behaviour in the EU context. Drawing on a literature survey and interviews, as part of the EU Carbon-CAP project, we develop a list of 33 potential instruments, present a systematic methodology for assessing their potential impact and feasibility, and apply this to rank instruments of most interest. Most instruments involve a clear trade-off between their potential impact and feasibility; about half feature in the top three scoring categories, many being voluntary approaches, which may be easier to implement, but with limited or highly uncertain impact. However, we identify a handful of top-scoring instruments that deserve far more policy attention. The complexity of consumer and corporate motivations and behaviours suggests that instruments should be trialled and monitored (e.g. in regions / individual States) before widespread introduction. Most would also be most effective when nested within wider policy packages, to address the varied behavioural motivations and stages of supply chains. Key policy insights Influencing consumer behaviour has been little used in climate policy and is politically sensitive and complex, but can address emissions that have largely escaped influence to date. A few instruments stand out as particularly promising, including: technology lists; supply chain procurement by leading retail companies; a carbon-intensive materials consumption charge; and key infrastructure improvements. A common trade-off between potential impact and likely feasibility points to the importance of government-business collaboration to secure support and impact. More ambitious transformation would require a mix of production and consumption-oriented policy instruments.